PARTISIPASI MASYARAKAT DALAM PENGELOLAAN TAMAN NARMADA DI KECAMATAN NARMADA KABUPATEN LOMBOK BARAT - Ni Putu Rika Sukmadewi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Narmada Park is one of the spiritual tourism attractions located in Lembuak Village, Narmada District, West Lombok Regency. Narmada Park is known as the Water Park for Youth. A uniqueness of Narmada Park is that the concept of this park is characterized by exotic natural nuances and around the park there are Kelasa Temple, pools, historic buildings (royal palace) and have historical legends. In its management, local community participation is needed so that in the future it can provide economic, socio-cultural and environmental benefits. The research method used is descriptive qualitative. The theory used in this research is Tosun's Typology of Participation (2006). Data collection is done through observation, interviews, and literature studies. The sampling technique uses purposive sampling technique. Data analysis techniques used are qualitative descriptive analysis such as, data reduction, data collection, and verification. The results showed that community participation in the management of Narmada Park was still in the induced participation phase. The characteristic of encouraged participation is that it is top down which means that local people will provide movement if there is direction from the government. Creativity in the form of an idea has been owned by several local communities but has not dared to take steps to overcome problems in the management of Narmada Park. Therefore, community empowerment is needed in increasing participation so that the management of Narmada Park can provide direct benefits to local communities in the region. Keywords: participation, community, management